Measurement Model of Social Capital, Entrepreneurial Orientation, Entrepreneurial Financing Choice and Performance in SMEs in West Sumatra - Siti Atikah Delfira; Erni Masdupi (Financial Management Studies, 2023)
This research provides evidence of a measurement model, (confirmatory factor analysis--CFA) of performance, social capital, entrepreneurial orientation, and entrepreneurial financing choice of SMEs in West Sumatra in 2023. The purpose of this research is to test the accuracy of the measurement model on the data that has been collected. To answer this research question using a structural equation model (SEM). With a sample of 342 SMEs, it was found that the hypothesized model is valid and significant. The highest SL performance indicators are on the 2nd indicator with a value of 0.0972 and the lowest SL is on the 5th indicator with a value of 0.517. The Social capital indicators the highest SL is on the 7th indicator with a value of 0.905 and the lowest SL is on the 1st indicator with a value of 0.496. The highest SL entrepreneurial orientation indicators are on the 3rd indicator with a value of 0.876 and the lowest SL is on the 9th indicator with a value of 0.600. The Entrepreneurial financing choice indicators the highest SL is on the 4th indicator with a value of 0.962 and the lowest SL is on the 1st indicator with a value of 0.565.